2012
DOI: 10.1016/j.arcontrol.2012.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and recent progress in the development of a closed-loop artificial pancreas

Abstract: Pursuit of a closed-loop artificial pancreas that automatically controls the blood glucose of individuals with type 1 diabetes has intensified during the past six years. Here we discuss the recent progress and challenges in the major steps towards a closed-loop system. Continuous insulin infusion pumps have been widely available for over two decades, but “smart pump” technology has made the devices easier to use and more powerful. Continuous glucose monitoring (CGM) technology has improved and the devices are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(107 citation statements)
references
References 136 publications
(152 reference statements)
0
106
0
1
Order By: Relevance
“…Sensor dropouts and attenuation, insulin infusion failure or erroneously announced meals are common issues encountered during typical AP operation [42]. The need to fulfill strict safety requirements has been evident in most AP designs and alternative software architectures have been evaluated.…”
Section: Software Architecturementioning
confidence: 99%
“…Sensor dropouts and attenuation, insulin infusion failure or erroneously announced meals are common issues encountered during typical AP operation [42]. The need to fulfill strict safety requirements has been evident in most AP designs and alternative software architectures have been evaluated.…”
Section: Software Architecturementioning
confidence: 99%
“…12 The challenge stems from that insulin delivered subcutaneous has a delayed onset and offset of action. 13 Premeal and correction boluses are still required with the 670G system.…”
Section: Diabetes Technology and Therapeuticsmentioning
confidence: 99%
“…These challenges include overcoming large meal disturbances, the effects of exercise, and the delays associated with subcutaneous glucose sensing and insulin delivery. 2 One of the most difficult aspects of the diabetes therapy routine is dealing with meals, and it has been shown that inaccurate estimation of meal sizes occurs frequently, resulting in additional glucose fluctuations. 3 Recent behavioral studies have also shown that people with T1DM are interested in an automated system but are concerned with relinquishing full control.…”
mentioning
confidence: 99%